Możliwości wykorzystania rówieśniczego tutoringu w edukacji dzieci z niepełnosprawnością intelektualną - Twardowski, Andrzej (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
Inclusion of able peers into the process of aiding the development of disabled children is beneficial for both groups. Able children have the opportunity to get to know disabled peers better, to understand them and to develop an accepting attitude toward them. Disabled children have the opportunity to learn that their able peers pay attention to them and are willing to play and talk to them. They also have a chance to experience that they can successfully influence other people. What is more, their autonomy increases since they have to relay more on themselves in interaction with peers. In the article the author analyzes the following issues: 1) theoretical basis of peer tutoring; 2) types of teaching interaction between children; 3) preparing the non-disabled peers for the role of tutors; 4) effectiveness of peer tutoring in teaching children with intellectual disabilities; 5) role of the teacher as an organizer of peer tutoring; 6) questions that require verification by future research. sification of the social issued and different possibilities of its interpretation. An important characteristic of this perspective is also the fact that it points out the need of trying to improve democracy. Like Laclau claims, “the moment of imagining of a desire is maybe more important than its accomplishing, because it is the moment that motivates us to action and initiates the creative thinking”.